Pemberdayaan Ekonomi Masyarakat Melalui Pembuatan Kripik Singkong Aneka Rasa di Dukuh Wonorejo Desa Bedrug - Al Nur Imam; Nanik Setyowati (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This article discusses efforts in the development of Small and Medium Enterprises (SMEs) in the field of rabbit farming in Pomahan Village, Pulong District, Ponorogo Regency. The aim of this research is to analyze the strategies employed in rabbit farming development and their impact on the economic empowerment of the local community. The research method utilized is a case study with a qualitative approach, involving in-depth interviews with rabbit farm owners.The research findings reveal that the rabbit farms in Pomahan Village have implemented strategies such as product diversification, employee training, and the utilization of information technology to enhance productivity and product quality. The resulting impacts include increased local community income, improved work skills, and economic empowerment through involvement in the local supply chain. Despite facing challenges like fluctuating feed prices and continuous weather changes.This article concludes that rabbit farmers in Pomahan Village play a significant role in driving the local economy and serve as an example of how diversification and innovation strategies can have a positive impact on rural community empowerment. This study is expected to provide valuable insights for the development of similar enterprises in other regions and serve as a reference for local economic empowerment policies.